Granzyme B: A new crossroad of complement and apoptosis - Perl, Mario; Denk, Stephanie; Kalbitz, Miriam; Huber-Lang, Markus (Current Topics in Innate Immunity II, 2012)
In response to severe tissue trauma, several "molecular danger" sensing and signaling pathways are activated, especially the complement and the apoptosis cascade. Although possible crossroads between both systems have been proposed, little is known about the underlying molecular interactions. In this study a new interaction interface is presented for C3a and C5a generation by the pro-apoptotic factor granzyme B. In vitro incubation of the central human complement components C3 and C5 with the serine protease granzyme B resulted in a concentration-dependent production of the anaphylatoxins C3a and C5a. The so generated anaphylatoxin C5a was chemotactic active for isolated human neutrophils. In a translational approach, intracellular granzyme B concentration in leukocytes was determined early after severe tissue trauma. In comparison to healthy volunteers, multiple injured patients (less than one hour after trauma, Injury Severity Score>18, n=5) presented a significant increase in granzmye B levels in neutrophils and lymphocytes. Thus, tissue trauma is associated with early activation of both, the complement and apoptosis system. The present data suggest a new form of interaction between the complement and the apoptosis system on the level of granzyme B that is capable to generate C3a and C5a independently of the established complement proteases.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Apoptosis; C3a; C5a; Complement; Granzyme B